Inventory Cost Comparison Using Continuous And Periodic Review Systems: Perbandingan Biaya Persediaan Menggunakan Sistem Peninjauan Berkelanjutan dan Periodik - Muhaimi, Muhammad Lutfi; Wulandari, Indah Apriliana Sari (Indonesian Journal of Innovation Studies, 2025)
General Background Inventory management plays a central role in maintaining production continuity and controlling operational costs in manufacturing systems. Specific Background Companies frequently apply Continuous Review and Periodic Review systems to determine optimal order quantities, reorder points, and safety stock levels in order to minimize total inventory cost. Knowledge Gap However, comparative empirical evaluation of both systems within a specific operational context remains limited, particularly in determining which policy generates lower total cost under actual demand conditions. Aims This study aims to analyze and compare the Continuous Review and Periodic Review methods to identify the inventory policy that produces the minimum total cost. Results The findings indicate differences in ordering frequency, safety stock levels, and total inventory cost, with one method demonstrating a lower overall cost based on calculated demand and cost parameters. Novelty The study provides a direct quantitative comparison of two widely applied inventory control systems within a single operational dataset. Implications The results offer practical guidance for managerial decision-making in selecting an appropriate inventory control policy to achieve cost efficiency and operational stability. Keywords: Inventory Management, Continuous Review System, Periodic Review System, Total Inventory Cost, Safety Stock Key Findings Highlights Comparative cost calculations reveal distinct ordering policies between the two control systems. Differences in reorder strategy generate variation in total inventory expenditure. Quantitative evaluation supports selection of a cost-minimizing policy for operational planning.